"If the Barn Is Burning, Let the House Burn as Well": Patterns of Drug Abuse Among FSU Immigrant Drug Addicts in Israel. (July 2016) - Liat, Yakhnich
This qualitative study focuses on the unique characteristics of drug abuse among former Soviet Union (FSU) immigrant drug addicts in Israel, as well as on special concerns faced by them during rehabilitation. It is based on in-depth interviews with Russian-speaking recovering addict counselors employed in addiction treatment centers. The findings point to the existence of a distinct "Russian" drug-abuse culture that is expressed through unique patterns of abuse, rapid deterioration, adherence to the "Russian" criminal moral code, and distinct norms of interpersonal relations. Furthermore, a complex relationship between this culture and the rehabilitation process was found, with cultural features having both negative as well as positive effects on patients' chances of successful recovery. A discussion is presented regarding the implications for treatment based on the interviewees' reflections as well as on existing literature.